1991
DOI: 10.1095/biolreprod45.3.493
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations in the Testis and Epididymis of Vizcacha (Lagostomus Maximus Maximus)1

Abstract: Seasonal changes in reproductive activity in the adult male vizcacha (Lagostomus maximus maximus), a South American rodent, were investigated. Monthly, for 2 yr, the animals were killed and decapitated during the night near their burrows in the vicinity of San Luis, Argentina. The testes, epididymides, and pineal glands were removed and used for biochemical and structural studies. Significant changes associated with seasonal cycles were found. 1) In July-August (winter in South America), a short hibernal perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
69
0
7

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(86 citation statements)
references
References 0 publications
10
69
0
7
Order By: Relevance
“…This is an efficient strategy to ensure energy metabolism and successful breeding as an adaptation to the annually changing conditions in their habitat [27]. Meanwhile, these findings were also similar to the observations in roe deer [23], viscacha [25,28] and mountain cavy [24]. In roe deer, the epididymal duct with its surrounding tissue expanded as the breading season approached.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…This is an efficient strategy to ensure energy metabolism and successful breeding as an adaptation to the annually changing conditions in their habitat [27]. Meanwhile, these findings were also similar to the observations in roe deer [23], viscacha [25,28] and mountain cavy [24]. In roe deer, the epididymal duct with its surrounding tissue expanded as the breading season approached.…”
supporting
confidence: 78%
“…The enlargement of the caput was primarily caused by growth of the epithelial compartment, whereas in the cauda, it was predominantly attributed to dilatation of the lumen [23]. In viscacha, the corpus and cauda were the most sensitive segments to changes induced by the photoperiod, and spermatogenesis did not cease during the regression period [25,28]. In mountain cavy, a decrease in the weight of the testis and epididymis was found during the nonbreeding season, which was independent of the change in body weight [24].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that the pineal gland and its hormone, melatonin, are involved in its reproductive rhythmicity (Domínguez et al, 1987;Fuentes et al, 1991;Pelzer et al, 1999;Muñ oz et al, 1999Muñ oz et al, , 2001Mohamed et al, 2000). Lascano et al (1999) demonstrated an avascular, rod-rich retina, with a specialized region spanning through most of the equator of the eye of the viscacha, suggesting that this equatorial region could be a highly sensitive light detector related to foraging behaviors during crepuscular or nocturnal hours.…”
mentioning
confidence: 99%
“…Much attention has been paid to the female germ line, since this species displays a number of unique and exceptional reproductive characteristics including massive polyovulation, abolished apoptosis-dependent germ cell attrition and follicular atresia, ovulation at mid-gestation and natural embryo selection in early post-implantation development [17][18][19][20]. However, male reproductive physiology in L. maximus has been mainly investigated by focusing on adult testicular changes related to the photoperiod, and endocrine variation caused by light/dark cycle fluctuation, which induces changes in the morphology of Leydig and Sertoli cells and spermatogonia [21][22][23][24][25]. Recently, we reported that the fetal testis of the South American plains vizcacha displays a distinctive pattern of development characterized by a sustained proliferation of germ cells with little or no apoptosis.…”
mentioning
confidence: 99%